A fast voltage sag detection method based on second order generalized integrator and delay transform method. (November 2022) - Wang, Ziming; Guo, Xiao; Li, Zhenyu; Lin, Hongyi; Chen, Guozhu
Abstract: Voltage sag is an important problem that causes power quality degradation, and the premise of solving the problem of voltage sag is to detect the depth of voltage sag accurately and quickly. Based on the past research on voltage sag detection, this paper proposes a voltage sag detection method that combines second order generalized integrator and delay transform method. Use the second order generalized integrator as the phase-locked loop and filter to extract the grid voltage phase angle and grid voltage fundamental wave, and then construct the quadrature component of the grid voltage fundamental wave by delaying a small angle. Square and square root calculation to quickly obtain voltage sag information. At the same time, the voltage sag information is used as the control signal of the second order generalized integrator to solve the problem of long response time of the second order generalized integrator. In this way, the interference of harmonics, zero-sequence and negative-sequence voltages on sag detection is excluded, and the rapidity of sag detection is ensured. Simulation and experiments show that the method can accurately and quickly determine the voltage sag depth.